Establishing nucleosome architecture and stability at promoters: Roles of pioneer transcription factors and the RSC chromatin remodeler. (27th March 2017) - Kubik, Slawomir; Bruzzone, Maria Jessica; Shore, David
Abstract : Improvements in deep sequencing, together with methods to rapidly deplete essential transcription factors (TFs) and chromatin remodelers, have recently led to a more detailed picture of promoter nucleosome architecture in yeast and its relationship to transcriptional regulation. These studies revealed that ∼40% of all budding yeast protein‐coding genes possess a unique promoter structure, where we propose that an unusually unstable nucleosome forms immediately upstream of the transcription start site (TSS). This "fragile" nucleosome (FN) promoter architecture relies on the combined action of the essential RSC (Remodels Structure of Chromatin) nucleosome remodeler and pioneer transcription factors (PTFs). FNs are associated with genes whose expression is high, coupled to cell growth, and characterized by low cell‐to‐cell variability (noise), suggesting that they may promote these features. Recent studies in metazoans suggest that the presence of dynamic nucleosomes upstream of the TSS at highly expressed genes may be conserved throughout evolution. Abstract : The size of nucleosome‐depleted regions (gray) at most yeast promoters (left) is determined by the abundance and distribution of PTF binding sites and RSC activation motifs (G/C‐rich and polyA), with regions >150 bp occupied by FNs (orange). Other promoters, often at highly inducible genes, utilize TFs to eject nucleosomes (right).